Perbandingan Pola Konsumsi Pangan Hewani antar Tiga Strata Pendapatan Rumah Tangga (Kasus pada Rumah Tangga Konsumen di Kecamatan Telanaipura, Jambi) - Mulyana, Sambas (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2010)
The goal of this research is to assess the consumptive pattern on animal origin food of consumers household in Kecamatan Telanaipura, Municipal of Jambi. Method of research conducted by survey. Thirty of consumers household was selected through stratified sampling based on three strata of household income : low income, middle income and high income. Data collected was data primer and secunder. Data analysed by descriptive method and One-Way Anova. The study indicated that there is different consumptive pattern on animal origin food of household consumer from three strata of income